Persoalan Corpus Delicti dalam Teologi Kristen tentang Persidangan Ilahi - Sonny Eli Zaluchu (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2020)
This study aims to examine and examine the concept of the divine trial regarding every human act at the end of time by using the Corpus Delicti perspective that was initiated by Erastus Sabdono regarding the fall of Lucifer. Corpus Delicti is a principle that emphasizes that a person cannot be punished unless proven guilty. It is concluded that in the concept of Christian theology, all people will actually stand before God, the Judge and all their deeds in the world are evidence for God to give rewards. The Corpus Delicti conception cannot be fully applied in Christian theology except definitively about its meaning. Because this term only and always refers to evil, whereas in Christian theology, divine commerce also includes good works. The analysis was carried out using the technique of fits biblical expectations, which is based on commentaries, conceptions, and views of theologians in books and journal papers. Abstrak Penelitian ini bertujuan menelaah dan meneliti konsepsi persidangan ilahi menyangkut setiap perbuatan manusia di akhir zaman dengan mengguna-kan cara pandang Corpus Delicti yang digagas oleh Erastus Sabdono mengenai kejatuhan Lucifer. Corpus Delicti adalah prinsip yang menekankan bahwa sese-orang tidak dapat dihukum kecuali dibuktikan bersalah. Disimpulkan bahwa di dalam konsep teologi Kristen, semua orang justru akan berdiri di hadapan Tuhan, Sang Hakim, dan semua perbuatannya di dunia adalah alat bukti bagi Tuhan untuk memberikan ganjaran. Konsepsi Corpus Delicti tidak dapat dipa-kai sepenuhnya di dalam teologi Kristen kecuali secara definitif tentang penger-tiannya. Sebab, istilah ini hanya dan selalu merujuk pada kejahatan sedangkan di dalam teologi Kristen, persidagangan ilahi juga mencakup perbuatan baik. Analisis dilakukan dengan teknik fits biblical expectations yang berpijak pada commentary, konsepsi dan padangan teolog di dalam buku dan paper jurnal.